Answer: The required solution is
[tex]y=(-2+t)e^{-5t}.[/tex]
Step-by-step explanation: We are given to solve the following differential equation :
[tex]y^{\prime\prime}+10y^\prime+25y=0,~~~~~~~y(0)=-2,~~y^\prime(0)=11~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
Let us consider that
[tex]y=e^{mt}[/tex] be an auxiliary solution of equation (i).
Then, we have
[tex]y^prime=me^{mt},~~~~~y^{\prime\prime}=m^2e^{mt}.[/tex]
Substituting these values in equation (i), we get
[tex]m^2e^{mt}+10me^{mt}+25e^{mt}=0\\\\\Rightarrow (m^2+10y+25)e^{mt}=0\\\\\Rightarrow m^2+10m+25=0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~[\textup{since }e^{mt}\neq0]\\\\\Rightarrow m^2+2\times m\times5+5^2=0\\\\\Rightarrow (m+5)^2=0\\\\\Rightarrow m=-5,-5.[/tex]
So, the general solution of the given equation is
[tex]y(t)=(A+Bt)e^{-5t}.[/tex]
Differentiating with respect to t, we get
[tex]y^\prime(t)=-5e^{-5t}(A+Bt)+Be^{-5t}.[/tex]
According to the given conditions, we have
[tex]y(0)=-2\\\\\Rightarrow A=-2[/tex]
and
[tex]y^\prime(0)=11\\\\\Rightarrow -5(A+B\times0)+B=11\\\\\Rightarrow -5A+B=11\\\\\Rightarrow (-5)\times(-2)+B=11\\\\\Rightarrow 10+B=11\\\\\Rightarrow B=11-10\\\\\Rightarrow B=1.[/tex]
Thus, the required solution is
[tex]y(t)=(-2+1\times t)e^{-5t}\\\\\Rightarrow y(t)=(-2+t)e^{-5t}.[/tex]